2013
DOI: 10.1186/1475-2840-12-142
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia induces differential change in oxidative stress at gene expression and functional levels in HUVEC and HMVEC

Abstract: BackgroundEndothelial dysfunction precedes pathogenesis of vascular complications in diabetes. In recent years, the mechanisms of endothelial dysfunction were investigated to outline strategies for its treatment. However, the therapies for dysfunctional endothelium resulted in multiple clinical trial failures and remain elusive. There is a need for defining hyperglycemia-induced endothelial dysfunction with both generic and specific dysfunctional changes in endothelial cells (EC) using a systems approach. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 57 publications
11
106
1
5
Order By: Relevance
“…This finding is consistent with a number of previous studies (31,39,44). It has been reported that hyperglycemia increases hydrogen peroxide production and downregulates CAT gene expression (55). A number of in vitro and in vivo studies have found varying responses of catalase to increased amount of ROS production induced by ZnO.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with a number of previous studies (31,39,44). It has been reported that hyperglycemia increases hydrogen peroxide production and downregulates CAT gene expression (55). A number of in vitro and in vivo studies have found varying responses of catalase to increased amount of ROS production induced by ZnO.…”
Section: Discussionsupporting
confidence: 82%
“…In this instance NOX activation in endothelial cells could be of importance. Patel et al [23] highlighted a unique framework for hyperglycemia-induced hydrogen peroxide production by NOX in endothelial cells and Hecker et al [24] found that an aberrant up-regulation of the isoenzyme NOX4 results in a sustained redox imbalance, which promotes persistent myofibroblast senescence and fibrosis. In this context it is of interest to note that pancreatic islets are among the most vascularized organs in the body with 1000-1500 capillaries per square millimeter, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia causes formation and accumulation of irreversible advanced glycation end products (AGEs) in the body 31) and induces expression of their primary receptor RAGE 32) . Interactions between the AGEs and RAGE result in the dysfunction of immune cells 6,7) and functional alterations of various cells 8,9) , causing cytokine imbalance associated with inflammatory cytokine increases 10,11) . Furthermore, hyperglycemia shifts the balance of the RANKL/OPG interaction in the direction of tissue destruction through AGEs/RAGE interaction 33,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, numerous mechanisms have been reported to underlie exacerbation of periodontitis caused by diabetes mellitus. Among them, the main mechanisms involve immune dysfunction 6,7 ) , cellular stress 8,9 ) , and cytokine imbalance 10,11) caused by hyperglycemia, which enhances tissue destruction of periodontitis and impairs tissue repair. The mechanism of exacerbation of alveolar bone resorption due to cytokine imbalance is initiated when hyperglycemia increases the level of inflammatory cytokines, such as TNF- 10) , IL-1 11) , and IL-6 11) .…”
Section: Introductionmentioning
confidence: 99%